Correlating Demographics and Well-being among Rural College Students in the Philippines - Resti Tito Villarino; Maureen Lorence Villarino; Maria Concepcion Temblor; Prosper Bernard; Michel Plaisent (Nurse Media Journal of Nursing, 2023)
Background: College students’ well-being is influenced by various factors such as age, gender, and socio-economic levels, but research findings on their correlation are inconsistent.Purpose: This study aimed to investigate the relationship between age, gender, socio-economic levels, and well-being among college students in private and state colleges in Cebu and Bohol, Philippines.Methods: The study employed a cross-sectional design and recruited 178 college students using convenient sampling. The modified Positive Emotion, Engagement, Relationship, Meaning, and Accomplishment (PERMA) profiler questionnaire was used to measure well-being. Data were analyzed using SPSS Statistics 27, and Kendall’s tau and point-biserial correlation coefficient were used for data analysis.Results: The overall PERMA score of the respondents (7.05±1.60) indicated high functioning. The analyses did not reveal a significant relationship between age and gender with well-being, but a significant association was found between socio-economic levels and the overall PERMA scores (p<0.05).Conclusion: The study’s findings suggest socio-economic levels significantly impact college students’ well-being. Therefore, interventions and policies targeting socio-economic factors may effectively promote well-being among college students.